Overexpression of Myrothamnus flabellifolia MfWRKY41 confers drought and salinity tolerance by enhancing root system and antioxidation ability in Arabidopsis - Huang, Zhuo; Song, Li; Xiao, Yao; Zhong, Xiaojuan; Wang, Jiatong; Xu, Wenxin; Jiang, Cai-Zhong (Frontiers in Plant Science, 2022)
Myrothamnus flabellifolia is the only woody resurrection plant discovered so far and could recover from extreme desiccation condition. However, few genes related to its strong drought tolerance have been characterized, and the underlying molecular mechanisms remains mysterious. Members of WRKY transcription factor family are effective in regulating abiotic stress responses or tolerance in various plants. An early dehydration-induced gene encoding a WRKY transcription factor namely MfWRKY41 was isolated from M. flabellifolia, which is homologous to AtWRKY41 of Arabidopsis. It contains a typical WRKY domain and zinc finger motif, and is located in the nucleus. Comparing to wild type, the four transgenic lines overexpressing MfWRKY41 showed better growth performance under drought and salt treatments, and exhibited higher chlorophyll content, lower water loss rate and stomatal aperture and better osmotic adjustment capacity. These results indicated that MfWRKY41 of M. flabellifolia positively regulates drought as well as salinity responses. Interestingly, the roots system, including lateral root number and primary root length, of the transgenic lines were enhanced by MfWRKY41 under both normal and stressful conditions, and the antioxidation ability was also significantly improved. Therefore, MfWRKY41 may have potential application values in genetic improvement of plant tolerance to drought and salinity stresses. The molecular mechanism involving in the regulatory roles of MfWRKY41 is worthy being explored in the future.